Supernumerary marker chromosome and global developmental delay: Role of microarray - case report and review of literature - Bachani, Sumitra; Dadhwal, Vatsla; Deka, Deepika (Indian Journal of Case Reports, 2019)
Small supernumerary marker chromosomes (sSMCs) are defined as structurally abnormal chromosomes that cannot be identified or characterized by conventional karyotype analysis and are generally equal in size or smaller than chromosome 20. Here, we present the molecular characterization of an sSMCs derived from chromosome 15 in prenatal diagnosis in a 38-years-old female